Proceedings. The 9th Russian-Korean International Symposium on Science and Technology, 2005. KORUS 2005.
DOI: 10.1109/korus.2005.1507696
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative plasma jet formation for acceleration of macroparticles

Abstract: The control methods of cinematic parameters of cumulative plasma jets (PJ) formed while exposing conical targets to high-energy radiation are considered. It is shown that realization of the principle of the forced Jet formation allows to increase the speed and pulse of the formed PJ considerably.For obtaining of high speed plasma jets, acceleration of macro-particles to hypervelocity it is suggested in work El] to use the action of high energy radiation to the profiled targets.The idea can be developed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Preliminary numerical research on the jet-formation beginning process conducted by the authors of present paper showed [28] that in the turn zone the flow character is considerably non-stationary, wave and quasiperiodic. Such behavior is characteristic for the viscous medium.…”
Section: Physics Of Hypercumulationmentioning
confidence: 67%
See 1 more Smart Citation
“…Preliminary numerical research on the jet-formation beginning process conducted by the authors of present paper showed [28] that in the turn zone the flow character is considerably non-stationary, wave and quasiperiodic. Such behavior is characteristic for the viscous medium.…”
Section: Physics Of Hypercumulationmentioning
confidence: 67%
“…1-2. It has been by far considered impossible [29][30][31]. In [35] a kind of novel W typed shape charge concept for annular jet was proposed.…”
Section: Physics Of Hypercumulationmentioning
confidence: 99%
“…As it was shown in [10] the length of such type of antenna about several hundreds meters are available ( figure 16). Also new physical principles of shaped charge design in applications to plasma antenna must be developed [29][30][31][32]. For example, academic prof. V.F.Minin [34] at the beginning of 1960 th discovered a new shaped charge with cylindrical liner [13,29].…”
Section: Future Investigationsmentioning
confidence: 99%
“…The methods of the magnetic fields generation (including laser light interaction with a conical target for plasma jet formation in a hypercumulative mode) up to ≈100 MGaus, higher than that in flux‐compression generators, were discussed in Refs. [12–15]. The history of high magnetic field generation are reviewed in Refs.…”
Section: Introductionmentioning
confidence: 99%